Characteristics of Sediments Deposition in Karimata Strait - Muhammad Trial Fiar Erawan; Tri Prartono; Ali Arman (Marine Science Department Diponegoro University, 2018)
Karimata strait connects South China Sea and Indonesia territorial seas where the strait current pattern is affected by west and east monsoon. This condition influences particles depositing sedimentation process in the strait. Lack information about sediment depositing rate at the straits dozens years ago makes this research is important to be conducted. This research was to estimate sediment depositing rate in the strait in two areas, near shore and off shore of Borneo. The research was conducted on June to September 2015 used coring sediment samples. Those samples were derived from Baruna Jaya VIII Ship Cruise on June 2015 that was collaborative research between Ministry of Marine and Fisheries Affairs of Indonesia and National Nuclear Center of Indonesia (BATAN).Samples were analyzed in the laboratory of Chemical and Ocean, Department of Environmental and Natural Resources, Center of Radiation and Isotope, National Nuclear Center of Indonesia (BATAN). Estimation of sediment depositing rate used natural isotope 210Pb. The study shows that the depositing rate of the nearest to Borneo area is about 0.92 kg.m-2.y-1 (1965) and increases to be 3.31 kg.m-2.y-1 (2009). The other area is about 0.08 kg.m-2.y-1 (1840) and increases to be 1.78 kg.m-2.y-1 (2010). This result implies that the sediment depositing rate at the nearest area to Borneo is higher than the off shore. Keywords: Near shore, off shore, Natural Isotop 210Pb, CRS (Constant Rate of Supply) model